2021
DOI: 10.1029/2020ea001584
|View full text |Cite
|
Sign up to set email alerts
|

VESIcal Part I: An Open‐Source Thermodynamic Model Engine for Mixed Volatile (H2O‐CO2) Solubility in Silicate Melts

Abstract: Understanding the solubility and degassing of volatiles in silicate melts is a crucial component of modeling volcanic systems. As dissolved components, volatiles (primarily 2 H E O and 2 CO E) affect magma viscosity, rheology, and crystal growth. In addition, due to the strong dependence of volatile solubility on pressure, measured volatile concentrations in preserved high-pressure melts (i.e., melt inclusions: liquid magma trapped within crystals at high pressure, then brought to the surface during an eruptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…For Cl and F, models A and B produce very similar trajectories, as these models predict similar amounts of solid fractionated. The solubility of pure CO2 and H2O calculated using the MagmaSat solubility model (Ghiorso and Gualda, 2015) implemented in VESIcal (Iacovino et al, 2021) for a best-fit to the observed major element path (see Supporting Fig. S11) is shown with a blue dashed line.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For Cl and F, models A and B produce very similar trajectories, as these models predict similar amounts of solid fractionated. The solubility of pure CO2 and H2O calculated using the MagmaSat solubility model (Ghiorso and Gualda, 2015) implemented in VESIcal (Iacovino et al, 2021) for a best-fit to the observed major element path (see Supporting Fig. S11) is shown with a blue dashed line.…”
Section: Discussionmentioning
confidence: 99%
“…6. a-c) Example degassing paths for three fissures, with open and closed system degassing paths calculated using MagmaSat (Ghiorso and Gualda, 2015) in VESIcal (Iacovino et al, 2021) for specific melt inclusions overlain. Vectors for different processes are shown in a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This exercise is comparable to when T, fO2, and Y = w m ST are taken as independent variables in a silicate melt + vapour assemblage and the dependent variable Z = P is calculated (e.g., Figure 4c). The effect of dissolved S is currently not included in such calculations, which include only H2O and CO2 (e.g., Newman and Lowenstern 2002;Papale et al 2006;Iacono-Marziano et al 2012;Ghiorso and Gualda 2015;Allison et al 2019;Iacovino et al 2021). Also, the effect fO2 on volatile speciation in the silicate melt and vapour is mostly ignored (but see Scaillet and Pichavant 2004;Wetzel et al 2015).…”
Section: Magma Ascent and Degassingmentioning
confidence: 99%